Understanding Contemporary Islamic Crises in the Middle East. The Issues beneath the Surface - E. Fuller, Graham (Leiden University Press, 2017)
Over the past decade the Middle East has undergone huge geopolitical shifts, including widespread war and violence, the collapse of numerous regimes, a changing American role, a restored Russian presence, and the emergence of ISIS. In this book Graham Fuller addresses the character of these shifts and how they will shape the future of this tumultuous region as well as the role of major outside powers.